Gun, submarine, and Switzerland - Ghosh, Murari, 1931-; Chakraborty, Dilip (Calcutta : Sribhumi Pub. Co., 1987)
On the controversial defense contracts of the Govt. of India
Keywords: Bofors, AB; India -- Armed Forces -- Procurement -- Corrupt practices; India -- Politics and government -- 1977-